Effect of capital structure and profitability on company values - Bulan Oktrima; Budi Sutrisno (Har Press Indonesia, 2023)
This study aims to determine the effect of capital structure and profitability on firm value with the debt to The study conducted an analysis of the effect of capital structure and profitability on firm value, focusing on the debt to equity ratio (DER) and return on assets (ROA) variables. The main objective of the research was to determine the partial and simultaneous effects of these variables on firm value. The data analysis was conducted using classical assumption tests, including the normality test, multicollinearity test, autocorrelation test, and heteroscedasticity test. Additionally, the analysis involved simple linear regression, multiple linear regression, hypothesis testing (t test and F test), and coefficient of determination test. This research adopted a quantitative research method since the data collected was in numerical form and the analysis was conducted using statistical tools. The type of data used in the study was secondary data, which was sourced from the annual financial reports published on the IDX and idnfinnancials websites. The results of the analysis revealed that the DER variable (X1) did not have a significant effect on firm value (Y), and the ROA variable (X2) also had no significant impact on firm value (Y). However, when analyzed simultaneously, both the DER and ROA variables were found to have a significant effect on Firm Value. These findings suggest that it is necessary to consider both capital structure and profitability when evaluating the firm value. The results of this study can be used by investors and financial analysts to make informed decisions when investing in Indocement Tunggal Prakarsa, Inc.